Uji Aktivitas Hipoglikemik Kombinasi Ekstrak Daun Ceplikan (Ruellia tuberosa L.) dan Glibenklamid pada Tikus Putih Jantan dengan Induksi Aloksan - Bunga Yuniasakti; Ika Purwidyaningrum; Mamik Ponco Rahayu (Fakultas Farmasi Universitas Setia Budi, 2014)
Diabetes mellitus is a disease or metabolic disorder characterized with high blood glucose level accompanied with carbohydrate, lipid and protein metabolism disorder as a result of insufficient insulin function. In this study, ceplikan (Ruellia tuberossa L.) leaves contained flavonoid, saponin, and tannin with hypoglycemic activity. This research aimed to find out the hypoglycemic effect of ceplikan leaf extract and glibencamide combination, the effective dose of combination, and to find out the comparison of hypoglicemic effect between single extract and combination use. The extract of ceplikan leaves was obtained using maceration method with ethanol 70% solvent. The diabetic condition of animal was obtained using monohidrate alloxane induction 100 mg/kg BW. The treatment groups were divided into 6: negative control group with CMC, positive control with glibenclamide (0.45mg/kg BW), single dose of ceplikan leaves extract (937.5 mg/kg BW), combination of ceplikan leaves extract and glibenclamide (25%:75%; 50%:50%; 75%:25%). The blood glucose level was measured using glucometer on the day-7, and day-14. The result of research showed that the combination of ceplikan leaves extract and glibenclamide had hypoglycemic activity with the effective doses of 50%:50% and 25%:75%). The combination of ceplikan leaves extract and glibenclamide had hypoglycemic effect lower than the single extract did.